Harga Diri Sebagai Prediktor Kecenderungan Narsistik Pada Pengguna Instagram: Retno Dian Veronica, Ditta Febrieta - Retno Dian Veronica; Ditta Febrieta (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2022)
The development of internet technology today is growing quite rapidly, especially on social media. On Instagram social media, individuals will find it easy to upload photos and hope to get likes or comments on their uploads. Uploading photos or videos with more frequent or excessive intensity shows behavior that leads to narcissistic tendencies.k This study aims to determine the effect of self-esteem on narcissistic tendencies in students using Instagram at Bhayangkara University, Greater Jakarta. The subjects of this study were 140 students using Instagram. The results showed that self-esteem was able to significantly influence narcissistic tendencies with values ​​of F=12,465 and p=0.001 (p<0.05). Based on these results, it can be concluded that self-esteem is able to influence narcissistic tendencies in students using Instagram at Bhayangkara University, Greater Jakarta by 8.3%, while the remaining 91.7% is influenced by other factors outside this study.